Assessing rice flour-starch-protein mixtures to produce gluten free sugar-snap cookies. (April 2016) - Mancebo, Camino M.; Rodriguez, Patricia; Gómez, Manuel
Abstract: The mixture of rice flours, starches and proteins is common in gluten-free bakery products such as bread or cake. The aim of this study was to determine the effects of starch and/or protein addition in rice flour gluten-free cookie quality. For this purpose, the hydration and oil absorption properties of flour-starch-protein mixtures, dough rheology and quality cookie parameters (thickness, final diameter, spread factor, texture, colour and acceptability) were analysed. Generally, protein incorporation increased hydration properties of the mixture and dough consistency, producing cookies with limited spreading in the baking time, lower hardness values and darker colour. In particular, protein addition reduced the width up to 8.4% and the hardness up to 10.60% (control versus 20% of protein inclusion). However, maize starch addition reduced hydration properties and gave rise to cookies with higher thickness and width, but the texture and colour were not affected by the starch. Cookies with higher protein content showed higher acceptability than cookies with higher starch content and no protein addition. Therefore, protein and starch can be used in order to adjust the desired cookie characteristics depending on the cookie formulation and the needs of manufacturers. Highlights: Protein addition increased hydration properties of the mixture and dough consistency. Starch addition increased cookie dimensions without affecting the texture or colour. Protein content reduced the cookie dimensions and hardness and boosted darker cookies. Starch or protein incorporation did not affect sensory acceptability.